2011
DOI: 10.1007/s11239-011-0593-6
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of cigarette smoking cessation on fibrin clot properties

Abstract: To examine the associations between cigarette smoking and preferable clot properties. Plasma fibrin clots from 21 randomly selected current smokers (n = 7), former smokers (n = 7) and non-smokers (n = 7) were analyzed, using scanning electron microscopy (SEM). With the use of the turbidimetric clotting and lysis assay in plasma, the maximum absorbance (MaxAbs(C), MaxAbs(L)) was measured and lysis time (Lys(50%)) was calculated. Smoking cessation significantly influenced fibrin fiber branching and density. Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…These include: direct toxic effects of chemicals in cigarettes, smoking increasing the viscosity of blood and deleterious effects on the mesenteric vasculature [ 13 ]. The epidemiological data reports positive associations, with consistent fi ndings from both case-control and cohort investigations.…”
Section: Environmental Factors Smokingsupporting
confidence: 57%
“…These include: direct toxic effects of chemicals in cigarettes, smoking increasing the viscosity of blood and deleterious effects on the mesenteric vasculature [ 13 ]. The epidemiological data reports positive associations, with consistent fi ndings from both case-control and cohort investigations.…”
Section: Environmental Factors Smokingsupporting
confidence: 57%
“…The most common comorbidities associated with impaired fracture repair are obesity, diabetes, smoking, and advanced age (17)(18)(19)(20)(21)(22)(23). Furthermore, these comorbidities are all associated with impaired fibrin clearance or fibrinolytic activity (24)(25)(26). Given that impaired fibrinolysis is a feature common to comorbidites associated with impaired fracture repair, we hypothesize that, although extravascular fibrin matrices may exert beneficial effects on fracture repair, persistent fibrin deposition may have deleterious effects on fracture repair.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of an internationally accepted (combined) standardized methodology has resulted in numerous different approaches being described in the literature, which varied considerably in terms of activator, the concentration of reagents, dilution of plasma and recorded measurements. Not surprisingly, when we performed a review of these published assays , we found large interlaboratory variation for the respective healthy control groups, including: lag times that ranged from 27 to 399 s; rates of lateral aggregation (slope) that ranged from 0.02 to 0.43 change in absorbance units per unit of time (min); and maximum absorbance that ranged from 0.32 to 1.22 absorbance units. This exceptionally large variation precludes interlaboratory comparison and prevents the establishment of normal and disease ranges, which are available for other CVD risk factors.…”
Section: Background and Aimmentioning
confidence: 95%